ANALISA FAKTOR FAKTOR YANG MEMPENGARUHI KONSERVATISME AKUNTANSI - Sari Rahmadhani; Arkanuddin Nur (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2015)
This study aims to provide empirical evidence regarding the effect ofmanagerial ownership, institutional ownership, leverage and financialdistress to accounting conservatism. Based on the test results show thatmanagerial ownership negatively affects conservatism. This shows thatthe managerial ownership of companies in Indonesia is still low,although the company will be more conservative because managers aremore conservative in maintaining investor confidence. Whileinstitutional ownership in manufacturing companies in Indonesia ishigh does not affect accounting conservatism, this is becauseinstitutional shares are not able to interfere with managers, so theinstitution has not been able to supervise the behavior of managersconservatism.